1983
DOI: 10.1152/ajprenal.1983.244.2.f140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphate deprivation on phosphate reabsorption in rat nephron: role of PTH

Abstract: The sites of enhanced phosphate (PO4) reabsorption after PO4 deprivation were investigated before and after infusion of parathyroid hormone (PTH) in acutely thyroparathyroidectomized rats. Animals were fed either a control PO4 diet (1.6% P) or a low PO4 diet (0.025% P) for 2 days or 7-10 days. In control rats, PTH decreased PO4 reabsorption in the proximal tubule, loop of Henle, and distal convolution. PO4 reabsorption in the proximal tubule was enhanced after 2 days of PO4 deprivation. In this group, proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Animals fed a low-phosphate diet have been reported to have a blunted phosphaturic response to PTH (23,29,36). To determine whether this response was intrinsic to the cells, wild-type cells were incubated in low-phosphate media (0.3 mM phosphate) for 24 h. Our prior studies indicated that the adaptation to low-phosphate media is complete by 24 h. Sodiumindependent phosphate transport did not differ between wildtype proximal tubule cells grown in DMEM/F-12 (0.39 Ϯ 0.09 and 0.34 Ϯ 0.08 nmol⅐mg protein Ϫ1 ⅐10 min Ϫ1 in the absence or presence of PTH, respectively) and wild-type cells grown in low-phosphate media (0.32 Ϯ 0.06 and 0.39 Ϯ 0.10 nmol⅐mg protein Ϫ1 ⅐10 min Ϫ1 in the absence or presence of PTH, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Animals fed a low-phosphate diet have been reported to have a blunted phosphaturic response to PTH (23,29,36). To determine whether this response was intrinsic to the cells, wild-type cells were incubated in low-phosphate media (0.3 mM phosphate) for 24 h. Our prior studies indicated that the adaptation to low-phosphate media is complete by 24 h. Sodiumindependent phosphate transport did not differ between wildtype proximal tubule cells grown in DMEM/F-12 (0.39 Ϯ 0.09 and 0.34 Ϯ 0.08 nmol⅐mg protein Ϫ1 ⅐10 min Ϫ1 in the absence or presence of PTH, respectively) and wild-type cells grown in low-phosphate media (0.32 Ϯ 0.06 and 0.39 Ϯ 0.10 nmol⅐mg protein Ϫ1 ⅐10 min Ϫ1 in the absence or presence of PTH, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Several prior studies in intact animals have indicated that the phosphaturic effect of PTH is blunted in animals adapted to a low-phosphate diet (23,29,36). The mechanism of this relative resistance to the phosphaturic effect of PTH is unknown but may be the result of specific biochemical changes in renal proximal tubule cells or changes in systemic factors that alter PTH signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Since such changes in urine are the hallmarks of dietary phos phorus restriction [19][20][21], we considered 0.3% phospho rus diet to be a phosphorus-restricted diet. 243 Serum immunoreactive PTH level in chronic renal failure rats was increased to 34.2 ± 2.83 pg/ml compared with that of sham-operated rats (24.0 ± 1.08 pg/ml) when fed with 0.6% phosphorus diet ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the PTH-stimulated increase in urinary P i excretion is blunted in P i -deprived animals (3,26,31,34). Both in vivo and in vitro studies in the adult animal have demonstrated that this adaptive increase in P i uptake is due to enhanced P i reabsorption within both the proximal convoluted tubules (PCT) (20,21,29,37,41) and segments beyond the PCT, most likely the proximal straight tubule (PST) (15,29,34,41). Furthermore, dietary P i deprivation in the adult animal is also associated with an increase in the maximal velocity (V max ) of apical brush-border membrane (BBM) sodium-dependent P i cotransport (NaPi) activity (4,18,20,21,24,25).…”
mentioning
confidence: 99%